(3cJGH GdYbGFO GdeHGQcIs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3bGd GdTjN eMji GdOjf CHh YHO Gddg eMeO Hf Ydi Hf eMeO GdWGFi GdMGJei QHeG hbY YfOi Cf CLYd ai gPG GdcJGH aUdkG ai GdYbGFO GdeDjOI HGdCOdI GdbWYjI hGdHQGgjf GdSGWYI s
(3BNQgG (B:s
(3hUfGYI GdJQcjH YfO QLhYgG HSfi GdhLhO Edi XdGe GdgGhjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B257s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI Ndjd GdNGdOi HGdbOS (B((3eLGejY (B1) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs